Biology, Ecology, and Management of Hemipteran Pests in Almond Orchards in the United States. Issue 1 (11th June 2021) - Rijal, Jhalendra P; Joyce, Andrea L; Gyawaly, Sudan
Abstract: Almond, Prunus dulcis (Miller) D. A. Webb, is an important tree nut crop cultivated primarily in the Mediterranean climatic regions. However, the United States, specifically the state of California, is the largest producer and exporter of almond nuts in the world. At least 60 species of insect pests attack almonds worldwide. Hemipterans can be important pests in almond orchards. Some hemipteran insect pests in almonds include lace bugs, plant bugs, stink bugs, and leaffooted bugs. These pests use needle-like mouthparts to pierce and feed upon fruits or other parts of the plant, causing direct or indirect crop damage. Nonetheless, the biology, life history, and management practices for many hemipteran pests of almonds are not available in the literature or come from research of these insects on other crops and host plants. In this article, we discuss the current understanding of biology, ecology, and management of hemipteran pests of almonds and outline future research to advance the integrated pest management of these pests in almond orchard systems.